Traditional free-weight vs. variable resistance training applied to elite young soccer players during a short preseason: effects on strength, speed, and power performance - Loturco, I.; Pereira, L. A.; Reis, V. P.; Zanetti, V.; Bishop, C.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2022)
Maximizing the neuromuscular capacities of players is a critical challenge during short soccer preseasons. This study compared the effects of 2 strength-power training regimes, on the strength, speed, and power performance of elite young soccer players during a 4-week preseason. Twenty-five under-20 players from the same club were pair matched in 2 training groups as follows: traditional training group (TTG) (n = 13), athletes performed half-squat (HS) and jump-squat (JS) exercises as traditionally prescribed, and elastic band (EB) group (EBG) (n = 12), athletes performed HS and JS with EB attached to the barbell. Vertical jump height, 20-m sprint velocity, change of direction (COD) speed, HS and JS power, and 1 repetition maximum (1RM) in the HS were assessed before, after 2-week, and after 4-week of training. A two-way analysis of variance with repeated measures was used to assess the effects of both training protocols over the experimental period. Both strategies were effective for significantly improving HS and JS power (effect sizes [ESs] = 1.00-1.77), HS 1RM (ES = 1.68 and 1.51 for TTG and EBG, respectively), vertical jumping ability (ES = 0.37-0.65), and COD speed (ES = 0.81 and 0.39 for TTG and EBG, respectively), when comparing premeasures and postmeasures. By contrast, both TTG and EBG failed to increase 20-m sprint velocity (ES ranging between -0.54 and 0.23). In conclusion, both training schemes were able to improve the strength and power performance but not the sprint capacity of young soccer players. To accelerate strength gains over very-short time periods (i.e., 2 weeks), variable resistance training may be advantageous. Conversely, to optimize power adaptations in ballistic exercises across a similar time period, traditional free-weight training may be preferred.